Late-epigenetic framboidal pyrites in deep-lying reservoirs of gas-condensate pools - Lukin, A.E.; Gafich, I.P. (Reports of the National Academy of Sciences of Ukraine, 2018)
The presence of framboidal pyrites within the pore space of deep-lying (4500-6500 m) secondary reservoirs of gas-condensate pools has been found. It belongs to the terminal late-epigenetic mineral new formations. This is not only the sign of specific tectonophysical and geothermobaric conditions at great depths, but the indicator of the processes of self-cleaning of deep-seated gas-c ondensate systems from hydrogen sulphide as a resul t of its reactions with Fe2+ cations of condensed hydrocarbon waters connected with the deep hydrogeologic inversion.